Immunological and clinical overlap between autoimmune gastritis and autoimmune liver diseases: a prospective cohort study - Massironi, Sara; Dispinzieri, Giulia; Rossi, Alberto; Cristoferi, Laura; Lenti, Marco Vincenzo; Gerussi, Alessio; Elvevi, Alessandra; Carbone, Marco; Bonfichi, Alessandra; Di Sabatino, Antonio; Danese, Silvio; Invernizzi, Pietro (Frontiers in Immunology, 2025)
BackgroundAutoimmune gastritis (AIG) and autoimmune liver diseases (AILDs)—including autoimmune hepatitis (AIH), primary biliary cholangitis (PBC), and primary sclerosing cholangitis (PSC)—are chronic organ-specific immune-mediated disorders. While both conditions frequently co-occur with other autoimmune diseases, the prevalence, clinical overlap, and immunological associations between AIG and AILDs remain underexplored.ObjectiveTo investigate the prevalence of AIG in patients with AILD and characterize the clinical, serological, and histopathological features of this overlap, to improve early detection and guide integrated management strategies.MethodsWe conducted a prospective study on 104 patients with a confirmed diagnosis of AILD. All participants were screened for anti-parietal cell antibodies (APCA); those testing positive underwent upper gastrointestinal endoscopy and gastric biopsies. Histological assessment was based on the updated Sydney System, with evaluation of mucosal inflammation, glandular atrophy, and intestinal metaplasia.ResultsAPCA positivity was observed in 22.1% of AILD patients, with a female predominance (78.3%). The median age of AIG diagnosis in APCA-positive patients was 58 years. Among APCA-positive individuals, histological confirmation of AIG was achieved in 91.3%, with a high rate of intestinal metaplasia (95.7%) and variable OLGA stages of gastric atrophy. Comorbid autoimmune conditions were common, with 43.5% of APCA-positive patients also presenting with autoimmune thyroiditis. Notably, PBC was disproportionately represented in the APCA-positive subgroup (47.8%) compared to the overall cohort (39.0%).ConclusionThis study highlights a clinically significant association between AIG and AILDs, particularly in patients with PBC and concurrent autoimmune conditions. Given the elevated risk of gastric mucosal atrophy and potential neoplastic transformation, targeted screening for AIG in AILD patients—especially those with APCA positivity or thyroid autoimmunity—should be considered. These findings underscore the importance of cross-specialty surveillance and open new avenues for research into shared immunopathogenic mechanisms.Lay SummaryThis study found that a significant number of patients with autoimmune liver diseases, especially those with primary biliary cholangitis, also show signs of autoimmune gastritis. These results support the consideration of targeted screening for gastric involvement in selected patients to improve early detection and clinical management of associated complications.